Modeling the Frequency and Severity of Extreme Exchange Rate Returns - Hsieh,Ping-Hung (Journal of Forecasting, 2001)
Risk managers are often concerned about tail probabilities of asset return distributions, in particular the frequency and severity of extreme returns. In this article, we propose a model that integrates extreme value theory and point processes to model the frequency and severity of exchange rate returns. The proposed model is applied to daily spot exchange rate series and the parameters of interest, such as the tail index, the mean size and rate of occurrence of extreme returns, are estimated using maximum likelihood estimation. We study the impact of recent currency crises on the frequency and severity of the series and find that, during 1995-9, the frequency of extreme daily Japanese yen-US dollar spot exchange rate returns increases twofold, and the time duration of high volatility persists longer for the Japanese yen series than for the Swiss franc and Danish krone series. Copyright © 2001 John Wiley & Sons, Ltd.
Keywords: Supply Chain